Mapping migration : culture and identity in the Indian diasporas of Southeast Asia and the UK - Daboo, Jerri, 1967-; Sinthuphan, Jirayudh (Cambridge Scholars Publishing, 2018)
This edited collection examines culture and identity in Indian diaspora communities in Southeast Asia, and the UK. Using methodologies such as transnational and diaspora studies, history, autoethnography and family histories, the contributions here explore the movements of people from the Indian subcontinent across generations to a wide range of countries. Cultural practices including the use of performance, food, rituals, religion, education, employment, and names demonstrate how identities and practices are preserved, as well as adapted, in new contexts. This offers original insights into tr.